Is Pakistan's Growth Rate Balance-of-Payments Constrained? Policies and Implications for Development and Growth - Jesus Felipe; J. S. L. McCombie; Kaukab Naqvi (Asian Development Bank (ADB), 2009)
This paper examines the extent to which Pakistan's growth has been, or is likely to be, limited or constrained by its balance-of-payments (BOP). The paper begins by briefly considering the BOP-constrained growth model in the context of demand and supply-oriented approaches to economic growth. Evidence presented suggests that Pakistan's maximum growth rate consistent with equilibrium on the basic balance is approximately 5% per annum. This is below the long-term target rate of a growth of gross domestic product of 7–8% per annum. This BOP-constrained growth approach provides some important policy prescriptions for Pakistan's development policy. Real exchange rate depreciations will not lead to an improvement of the current account. Pakistan must lift constraints that impede higher growth of exports. In particular, it must shift its export structure to products with a higher income elasticity of demand and sophistication.
hdl:11540/1813
Keywords: 330; Zahlungsbilanz; Wirtschaftswachstum; Entwicklungspolitik; Pakistan